Efektivitas Mobilisasi Dini terhadap Percepatan Pemulihan Fungsi Fisik pada Ibu Pasca Operasi Sectio Caesarea - Wilda Arifia Nuraeni; Tiara Fatmarizka; Arif Abdullah (CV. ALIM'SPUBLISHING, 2026)
Background: Sectio caesarea can delay physical function recovery in postpartum mothers, affecting daily activities. Early mobilization is an intervention that may accelerate recovery. Purpose: To analyze the effectiveness of early mobilization in accelerating physical function recovery in post-sectio caesarea patients at RS Muhammadiyah Selogiri. Method: Quasi-experimental design with a non-equivalent control group pretest-posttest design. Thirty-four postpartum mothers were divided into intervention (n=17) and control (n=17) groups. The Barthel Index, Numeric Rating Scale (NRS), and observation sheets were used. Results: The intervention group showed faster recovery with significant improvements in Barthel Index scores, time to ambulate independently, and pain reduction (p<0.001). Conclusion: Early mobilization effectively accelerates physical function recovery in post-sectio caesarea patients.